2017
DOI: 10.1063/1.4985630
|View full text |Cite
|
Sign up to set email alerts
|

Local structure of dilute aqueous DMSO solutions, as seen from molecular dynamics simulations

Abstract: The information about the structure of dimethyl sulfoxide (DMSO)-water mixtures at relatively low DMSO mole fractions is an important step in order to understand their cryoprotective properties as well as the solvation process of proteins and amino acids. Classical MD simulations, using the potential model combination that best reproduces the free energy of mixing of these compounds, are used to analyze the local structure of DMSO-water mixtures at DMSO mole fractions below 0.2. Significant changes in the loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 70 publications
(98 reference statements)
0
20
0
Order By: Relevance
“…Based on modeling, the congurations of different types of clusters have been shown. [9][10][11][12] The expanded range of the glass transition of water was found via the molecular dynamics annealing simulations. This would correspond to the formation of a stronger glass in water-DMSO mixtures 13 and it brings some new insights into the mechanism of cryoprotection at the molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…Based on modeling, the congurations of different types of clusters have been shown. [9][10][11][12] The expanded range of the glass transition of water was found via the molecular dynamics annealing simulations. This would correspond to the formation of a stronger glass in water-DMSO mixtures 13 and it brings some new insights into the mechanism of cryoprotection at the molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…Binary mixtures of DMSO and other co-solvents are also known to be heterogeneous. [10][11][12][13] In the case of DMSO-water mixture, the maximum deviation from the ideal mixing behavior occurs around 33% mole fraction of DMSO. 10 The existence of different types of aggregates in the DMSO-water mixture is believed to be the reason behind this heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that acid will get dissociated in a particular solvent if the stability of the dissociated acidsolvent cluster is greater than the stability of the undissociated acid-solvent cluster. [11][12][13][14][15][16] However, it was shown that the acid dissociation mechanism of HCl in water and reported that the stabilization energy of the HCl-water cluster is not the only criteria for the acid to be dissociated in water, and the orientation of the water molecules around the HCl molecule also plays a pivotal role in the acid dissociation process. 14 It was also reported that in some HCl-water clusters the HCl remains undissociated, even though in those structures the number of water molecules and their stabilization energy were almost identical to the dissociated HCl-water clusters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Binary mixtures of DMSO and other co-solvents are also known to be heterogeneous. [10][11][12][13] In the case of DMSO-water mixture, the maximum deviation from the ideal mixing behavior occurs around 33% mole fraction of DMSO. 10 The existence of different types of aggregates in the DMSO-water mixture is believed to be the reason behind this heterogeneity.…”
Section: Introductionmentioning
confidence: 99%